How Indonesian Coconut Oil Competes in China: La/Aids Model Approach - Fitri, Febti Aulia; Noval, Bahieddin (Journal of Agriculture, 2025)
Coconut oil is a promising commodity for Indonesia, with increasing global demand in the last decade. Indonesia must take advantage of this moment by increasing its competitiveness. This study aims to analyze the competitiveness of coconut oil exports relative to rival products in the Chinese market. The research uses secondary data from 1993 to 2022 and is analyzed using the LA/AIDS demand model. The findings indicate that Indonesian coconut oil has a 50% demand share and is the highest in the Chinese market. The elasticity of expenditure is 1.58 (E > 1), indicating it is elastic and of the best quality. According to the own-price elasticity, Indonesian coconut oil is negative (-1.532), so it is elastic and experiences a decrease in demand when the price increases. Meanwhile, the cross-price elasticity is positive, indicating that the relationship between Indonesian and Philippine coconut oil is substitutive or competitive. Indonesia and Malaysia show a complementary relationship. However, when viewed in reverse, it shows a substitution relationship. Based on this analysis, Indonesia has the opportunity to control the coconut oil trade in the Chinese market and potentially in other markets if it can optimize its competitiveness.